2019
DOI: 10.2196/11575
|View full text |Cite
|
Sign up to set email alerts
|

An App to Improve Eating Habits of Adolescents and Young Adults (Challenge to Go): Systematic Development of a Theory-Based and Target Group–Adapted Mobile App Intervention

Abstract: Background Due to the widespread use of mobile phones, dietary mobile apps are promising tools for preventing diet-related noncommunicable diseases early in life. However, most of the currently available nutrition apps lack scientific evaluation and user acceptance. Objective The objective of this study was the systematic design of a theory-driven and target group–adapted dietary mobile app concept to promote healthy eating habits with a focus on drinki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…These studies found the COM-B and TDF useful to inform an intervention to promote behaviour. Furthermore, studies have designed dietary interventions based on the COM-B model to promote the Mediterranean diet in adults at risk of CVD (28) , an app to improve eating habits of adolescents and young adults (29) and a text messaging service targeting healthy eating for children in a family intervention (30) . This study investigates the perceived barriers and facilitators to adopting the MIND diet in midlife (40-55 years).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These studies found the COM-B and TDF useful to inform an intervention to promote behaviour. Furthermore, studies have designed dietary interventions based on the COM-B model to promote the Mediterranean diet in adults at risk of CVD (28) , an app to improve eating habits of adolescents and young adults (29) and a text messaging service targeting healthy eating for children in a family intervention (30) . This study investigates the perceived barriers and facilitators to adopting the MIND diet in midlife (40-55 years).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The WHO emphasizes that unhealthy diets and physical inactivity are two key risk factors to develop non-communicable diseases such as, cardiovascular diseases, cancer, and diabetes [ 3 ]. In addition, the intake of fruits and vegetables in the child population is under the recommended levels and that of sugar is well above the established limits, which increases the risk of developing these diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty of inducing lifestyle changes in the young population, gamification can be an effective method to create change and improve adherence to healthy practices [ 6 ]. Some studies find that childhood is the ideal age to promote healthy habits, and resources such as social networks, mobile devices, or games can be very useful to promote knowledge and improve adherence [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction is generally considered to be the most attenuated outcome measure for patient-centered mHealth technologies and thus can likely be assessed from a purely descriptive [69] quantitative point of view, devoid of any thematic nuancing that qualitative measures can afford. There are numerous quantitative measures available to evaluate patient satisfaction, although the validity and reliability of the instruments have been a point of debate [69][70][71][72][73][74][75][76][77][78][79][80]. Patient Journey Mapping Tool [49,50] Impact of Assistive Devices Scale (PIADS) [51] Semistructured interviews Think aloud exercises…”
Section: Patient Satisfactionmentioning
confidence: 99%